2004
DOI: 10.1128/iai.72.12.6846-6851.2004
|View full text |Cite
|
Sign up to set email alerts
|

Resistance ofMycoplasma pulmonisto Complement Lysis Is Dependent on the Number of Vsa Tandem Repeats: Shield Hypothesis

Abstract: The Vsa proteins are associated with the virulence of the murine respiratory pathogen Mycoplasma pulmonis. The antigens consist of a conserved N-terminal region that is combined with one of several different variable C-terminal regions comprised of tandem repeats. M. pulmonis strains that produce VsaA with about 40 tandem repeats do not adhere to polystyrene or erythrocytes and are highly resistant to complement killing. Strains that produce VsaA with three tandem repeats adhere strongly to polystyrene and ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 31 publications
2
56
0
Order By: Relevance
“…It was possible that analysis by immunoblotting would have revealed that, over time, isolates gain an even larger number of tandem repeats to avoid the complement system. However, because the initial inoculum produced a Vsa protein with a large number of tandem repeats, the mycoplasma was already resistant to complement lysis (26), and no selection pressure was evidently present to promote further expansion of the tandem repeats. If the initial inoculum had been a mycoplasma population producing a Vsa protein with few tandem repeats, it is hypothesized that size variation would have occurred over time to generate mycoplasmas with a large number of tandem repeats to acquire resistance to complement killing or the growth-inhibitory effects of specific antibody (6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was possible that analysis by immunoblotting would have revealed that, over time, isolates gain an even larger number of tandem repeats to avoid the complement system. However, because the initial inoculum produced a Vsa protein with a large number of tandem repeats, the mycoplasma was already resistant to complement lysis (26), and no selection pressure was evidently present to promote further expansion of the tandem repeats. If the initial inoculum had been a mycoplasma population producing a Vsa protein with few tandem repeats, it is hypothesized that size variation would have occurred over time to generate mycoplasmas with a large number of tandem repeats to acquire resistance to complement killing or the growth-inhibitory effects of specific antibody (6).…”
Section: Resultsmentioning
confidence: 99%
“…Vsa size variation is thought to occur by slipped-strand mispairing within the tandem repeats of the vsa gene during DNA replication and has been shown to have a role in modulating the susceptibility of the cell to complement lysis. Isolates with a large number of tandem repeats are resistant to complement-mediated killing, whereas isolates with few tandem repeats are susceptible (26,27).Previous work in our laboratory noted that in rats infected intranasally with a strain of M. pulmonis that produced VsaA, selection pressures caused a shift of the mycoplasma population toward cells that produced a Vsa protein other than VsaA. Switching of the Vsa protein that was produced occurred in the lower respiratory tract but not in the nose (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are no known two-component regulatory systems or other recognizable global regulators in most species of mycoplasmas, including Mycoplasma pulmonis. The lack of such regulators can be attributed to the survival of the mycoplasmas in only one environmental niche: the animal host.The variable surface antigen (Vsa) proteins of the murine respiratory pathogen M. pulmonis are associated with virulence (34) and mediate the susceptibility of the mycoplasma cells to complement (26,27). A Vsa protein contains a conserved N-terminal region attached to one of several C-terminal tandem repeat regions (3, 28).…”
mentioning
confidence: 99%
“…Independent of the particular vsa gene that occupies the vsa expression site, mycoplasmas that produce a long form of the Vsa protein of about 40 tandem repeats do not adhere to polystyrene or erythrocytes. These mycoplasmas are resistant to killing by complement (26,27). Mycoplasmas that produce a short Vsa protein with only a few tandem repeats (e.g., five repeats or less) adhere to polystyrene, adsorb erythrocytes, and are efficiently killed by complement.…”
mentioning
confidence: 99%